A new species of lizard of the Liolaemus elongatus clade (Reptilia: Iguania: Liolaemini) from Curi Leuvu River Valley, northern Patagonia, Neuquén, Argentina - Avila, Luciano Javier; Perez, Cristian Hernan Fulvio; Medina, Cintia Debora; Sites, Jr., Jack Walter; Morando, Mariana (Zootaxa, 2012)
A new species of the Andean-Patagonian Liolaemus elongatus clade is described. Liolaemus burmeisteri sp. nov. differs from other members of its clade in a character combination of light brown general coloration, plain dorsal pattern, dark lateral areas, a very bright orange-yellow coloration on femoral area and lower belly, and other morphological and genetic traits. It is distributed on a restricted area on sedimentary rocky outcrops found in an intermountain valley. Liolaemus burmeisteri sp. nov. is known only for its type locality in Curi Leuvu River Valley in northwestern Patagonia above 1037 m. A mitochondrial DNA gene tree analysis found this new species as the sister taxon of Liolaemus smaug.